P137 19 f-mri of inhaled perfluoropropane gas: a novel approach to ventilation imaging. (15th November 2017) - Pippard, B; Neal, M; Dutta, P; Simpson, AJ; Thelwall, P
Abstract : Introduction: Current measures of pulmonary ventilation are beset by limitations. For example, spirometry provides no regional or anatomical information regarding lung function, while both CT and V/Q scans incur ionising radiation doses, restricting serial use. Hyperpolarised gas MRI (e.g., using 3 He and 129 Xe) enables direct assessment of airway structure and function without recourse to ionising radiation, but is confined to centres with access to specialised hyperpolarising equipment and expertise. A novel approach, involving 19 F-MRI of inhaled perfluoropropane gas, has recently been described in humans, 1, 2 offering an alternative to hyperpolarisation with scope for translation to clinical practice. Aim: We assessed the feasibility of using inhaled perfluoropropane gas to image pulmonary ventilation properties in a group of healthy volunteers. Methods: 17 participants (10 M, 7 F; aged 21–52) provided written informed consent, and were screened for normal lung function using standard spirometry. Participants were invited to attend two MRI scanning sessions, during which they inhaled a 79% perfluoropropane/21% oxygen gas mixture on up to three occasions. Gas inhalations lasted <1 min, typically involving 3–5 deep breaths followed by breath-hold. MRI scans of inhaled perfluoropropane were acquired using a Philips Achieva 3T scanner and a designated receiver coil tuned to 19 F frequency. Heart rate and oxygen saturations were monitored throughout. Results: In total, 94 gas inhalations were performed across 17 participants. Ventilation images were obtained within a single breath-hold, demonstrating homogeneous gas distribution throughout the lungs (figure 1 ). Inhalation of the gas mixture was well tolerated with no significant adverse events, other than a transient (seconds) fall in SpO2 (89%) following one breath-hold. This resolved spontaneously, and was not considered clinically significant. Conclusions: 19 F-MRI of inhaled perfluoropropane gas represents a novel approach to ventilation imaging, with potential for high quality image acquisition within a single breath-hold. Crucially, this technique can be implemented on MRI scanners with considerably less additional hardware than required for hyperpolarised gas MRI. Ongoing optimisation of scan protocols will enable further improvements in both spatial and temporal resolution, providing a platform for future clinical application. References: Couch MJ, et al. Radiology2013;269:903–909. Halaweish AF, et al. Chest2013;144:1300–1310.